UKRAINIAN DEFENSE INDUSTRY UNDER ECONOMIC SANCTIONS IS WITHIN THE RUSSIA'S INTERESTS - V. A. Mal’Gin (Russian Journal of Economics and Law)
Objective: to analyze a correlation between the Russian and the Ukrainian military-industrial complexes (MIC), as well as to determine possibilities for product substitution under economic sanctions. Methods: analysis and synthesis, statistical, abstract logic methods. Results: аn interdependence of Ukrainian and Russian military-industrial complexes is revealed; the role of economic sanctions as one of the important instruments and two-edged instruments of foreign policy is shown; the means of acceleration of development of defense-industrial complex of Russia are proposed. Scientifi c novelty: the article proves that the Ukrainian defense-industrial complex under economic sanctions represents serious threat to Russian military-industrial complex. The most effective ways of substituting the Ukrainian defense production by the Russian production are determined. Practical value: the proposed measures for substituting the Ukrainian military production by the Russian production will, under economic sanctions, contribute to Russia's further strengthening of military-industrial complex and the enhancement of operational capability of its armed forces.